Involvement of astrocytes in Alzheimer’s disease from a neuroinflammatory and oxidative stress perspective (2017)
Alzheimer disease (AD) is a frequent and devastating neurodegenerative disease in humans, but still no curative treatment has been developed. Although many explicative theories have been proposed, precise pathophysiological mechanisms are unknown. Due to the importance of astrocytes in brain homeostasis they have become interesting targets for the study of AD. Changes in astrocyte function have been observed in brains from individuals with AD, as well as in AD in vitro and in vivo animal models. The presence of amyloid beta (A?) has been shown to disrupt gliotransmission, neurotransmitter uptake, and alter calcium signaling in astrocytes. Furthermore, astrocytes express apolipoprotein E and are involved in the production, degradation and removal of A?. As well, changes in astrocytes that precede other pathological characteristics observed in AD, point to an early contribution of astroglia in this disease. Astrocytes participate in the inflammatory/immune responses of the central nervous system. The presence of A? activates different cell receptors and intracellular signaling pathways, mainly the advanced glycation end products receptor/nuclear factor kappa-light-chain-enhancer of activated B cells (NF-?B) pathway, responsible for the transcription of pro-inflammatory cytokines and chemokines in astrocytes. The release of these pro-inflammatory agents may induce cellular damage or even stimulate the production of A? in astrocytes. Additionally, A? induces the appearance of oxidative stress (OS) and production of reactive oxygen species and reactive nitrogen species in astrocytes, affecting among others, intracellular calcium levels, NADPH oxidase (NOX), NF-?B signaling, glutamate uptake (increasing the risk of excitotoxicity) and mitochondrial function. Excessive neuroinflammation and OS are observed in AD, and astrocytes seem to be involved in both. The A?/NF-?B interaction in astrocytes may play a central role in these inflammatory and OS changes present in AD. In this paper, we also discuss therapeutic measures highlighting the importance of astrocytes in AD pathology. Several new therapeutic approaches involving phenols (curcumin), phytoestrogens (genistein), neuroesteroids and other natural phytochemicals have been explored in astrocytes, obtaining some promising results regarding cognitive improvements and attenuation of neuroinflammation. Novel strategies comprising astrocytes and aimed to reduce OS in AD have also been proposed. These include estrogen receptor agonists (pelargonidin), Bambusae concretio Salicea, Monascin, and various antioxidatives such as resveratrol, tocotrienol, anthocyanins, and epicatechin, showing beneficial effects in AD models. © 2017 González-Reyes, Nava-Mesa, Vargas-Sánchez, Ariza-Salamanca and Mora-Muñoz.